2006
DOI: 10.3748/wjg.v12.i36.5884
|View full text |Cite
|
Sign up to set email alerts
|

ECA39 is a novel distant metastasis-related biomarker in colorectal cancer

Abstract: AIM:To investigate the possible role of polysaccharide-K (PSK) -related markers in predicting distant metastasis and in the clinical outcome of colorectal cancer (CRC). METHODS: Firstly, we used protein microarrays toanalyze the in vitro expression profiles of potential PSKrelated markers in the human colorectal adenocarcinoma cell line SW480, which carries a mutant p53 gene. Then, we investigated the clinical implications of these markers in the prognosis of CRC patients.RESULTS: ECA39, a direct target of c-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Depletion of BCAT1 by RNA interference in nasopharyngeal cancer cells effectively blocked the proliferation of cells suggesting a role for BCAT1 in tumorigenesis [79]. In colorectal cancer immuno-histochemical analysis of BCAT1 protein showed significantly higher levels of expression in tumor tissues with distant metastasis compared to those without and was shown to be highly predictive of distant metastasis [80]. The Casc1 gene was identified as a strong candidate lung tumor susceptibility gene through whole genome analyses in inbred mice [81].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of BCAT1 by RNA interference in nasopharyngeal cancer cells effectively blocked the proliferation of cells suggesting a role for BCAT1 in tumorigenesis [79]. In colorectal cancer immuno-histochemical analysis of BCAT1 protein showed significantly higher levels of expression in tumor tissues with distant metastasis compared to those without and was shown to be highly predictive of distant metastasis [80]. The Casc1 gene was identified as a strong candidate lung tumor susceptibility gene through whole genome analyses in inbred mice [81].…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, mRNA expression levels and immunohistochemistry have shown that Bcat1 over expression is a sensitive marker of metastases in medullablastoma 16 and colorectal cancer. 35 Fast in vivo assays of branched chain amino acid metabolism should be of interest for cancer diagnosis and prognosis. Our finding of largely increased branched chain amino acid metabolism in EL4 but not in R3230AC tumors in vivo is in principal agreement with previous reports of increased BCAT mRNA transcription in specific tumor lines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, BCATc was identified as a c-myc target in nasopharyngeal carcinoma and BCATc overexpression induced cancer cell proliferation and migration [92] . Although the majority of these studies imply that cancer cells require BCAA metabolism to sustain growth, and overexpression of BCATc results in increased cell proliferation [92,93] , the mechanism through which changes in BCAA metabolism affect cancer growth is currently unknown. It is possible that T cells and cancer cells share similar requirements for BCAA catabolism, where mTOR pathway is dependent on leucine regulation.…”
Section: Emerging Role Of Branched Chain Amino Acid Metabolism In Canmentioning
confidence: 99%